Deviations from cooperative growth mode during eutectoid transformation: Mechanisms of polycrystalline eutectoid evolution in Fe–C steels. (15th September 2015) - Ankit, Kumar; Mukherjee, Rajdip; Nestler, Britta
Abstract: Undercooling (below A 1 temperature) and spacing between the preexisting cementite particles are known to be the factors that determine whether the isothermal eutectoid transformation in Fe–C proceeds in cooperative (resulting in lamellar pearlite) or non-cooperative mode (yielding divorced eutectoid). Typically, a divorced eutectoid microstructure consists of a fine dispersion of cementite in the ferritic matrix. Although, numerous experimental studies report a bimodal size distribution of cementite in the transformed eutectoid microstructure, the factors that facilitate the shift from a characteristic unimodal to bimodal size distribution have not been reported extensively. In the present work, we adopt a multiphase-field approach to study the morphological transition during isothermal eutectoid transformation which proceeds from an initial configuration comprising of a random distribution of cementite particles and grain boundary ferrite layers embedded in polycrystalline austenite. By conducting a systematic parametric study, we deduce the influence of preexisting arrangement of cementite, grain boundary ferrite thickness and prior austenite grain size on the mechanism by which eutectoid phases evolve. We also establish a synergy between the numerically simulated cementite morphologies and spatial configurations with those observed in experimental microstructures. Finally, we discuss the influence of the different factors that lead to the formation of mixed cementite morphologies (spheroidal and non-spheroidal) in the transformed microstructure and highlight the importance of 3D simulations.